FEAR-DRIVEN DECISION-MAKING IN CYBER RISK MANAGEMENT AND DIGITAL TRANSFORMATION OF BANKING: A SYSTEMATIC LITERATURE REVIEW - Mataram, M Dedy Ompi; Mulyanti, Rita; Achmadi, Achmadi (LPPM Universitas Jambi, 2026)
This study employs a Systematic Literature Review (SLR) approach to examine fear-driven decision-making in cyber risk management and digital transformation within the banking sector. The review follows the PRISMA framework and analyzes 25 peer-reviewed journal articles selected from Scopus and Web of Science databases published between 2020 and 2025. The findings reveal that fear operates as a latent psychological mechanism influencing strategic decision-making, particularly through risk amplification, regulatory pressure, and trust concerns. Fear-driven responses often lead to conservative strategies, delayed innovation, and excessive risk aversion, which may affect organizational resilience and governance effectiveness. This study contributes to the literature by explicitly conceptualizing fear as a central construct in cyber risk management and digital transformation, providing both theoretical insights and practical implications for banking institutions.